2022
DOI: 10.3889/oamjms.2022.10235
|View full text |Cite
|
Sign up to set email alerts
|

Parental Sociodemographic Factors Associated with Stunted Children below 5 Years of Age in Kampar Indonesia

Abstract: BACKGROUND: The prevalence of stunted children under 5 years in Riau Province exceeds 27.35% and Kampar District contributed the highest prevalence rate (32.05%) compared to other districts in Riau Province. AIM: This study aims to analyze the parental sociodemographic factors of parents associated with stunting children in Kampar District, Riau Province in Indonesia. METHODS: This type of research is a case-control study on stunted children in Kampar Regency aged under 5 years. Control group was selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…This study claimed that parenting activities related to the development of children are more the responsibility of mothers than fathers, demonstrating that mothers' education and knowledge have an inverse relationship with the short stature of children in this case-control study (27). These ndings were also con rmed by our ndings and were consistent with those of similar studies in Indonesia, Rwanda, Ethiopia and sub-Saharan Africa (28),( 29), (30), (31), (32). Although a previous study showed that there was no relationship between stunting and maternal education level in Pakistan (33), some surveys acknowledged that educated parents can decrease the possibility of stunting in children (25).…”
Section: Parental Educationsupporting
confidence: 92%
“…This study claimed that parenting activities related to the development of children are more the responsibility of mothers than fathers, demonstrating that mothers' education and knowledge have an inverse relationship with the short stature of children in this case-control study (27). These ndings were also con rmed by our ndings and were consistent with those of similar studies in Indonesia, Rwanda, Ethiopia and sub-Saharan Africa (28),( 29), (30), (31), (32). Although a previous study showed that there was no relationship between stunting and maternal education level in Pakistan (33), some surveys acknowledged that educated parents can decrease the possibility of stunting in children (25).…”
Section: Parental Educationsupporting
confidence: 92%